LNP-enclosed NamiRNA inhibits pancreatic cancer proliferation and migration via dual pathways - Chao Yu; Zhou Fang; Qingyu Xie; Zhuo Wu; Peixian Huang; Jinlong Yu; Rufu Chen (Journal of Nanobiotechnology)
Abstract Background Pancreatic cancer is a highly aggressive malignancy characterized by limited treatment options, poor prognosis, and high mortality rates. nuclear activating miRNA (NamiRNA) enhances gene expression by interacting with nuclear enhancers, offering a novel avenue for understanding gene regulation in cancer. This study explores the dual role of mir-200c in regulating tumor proliferation and migration in pancreatic cancer, with the aim of identifying potential therapeutic strategies. Results Mir-200c significantly activated PTPN6 transcription via the NamiRNA-enhancer pathway, reducing tumor proliferation. Deletion of the enhancer sequence abolished the activation of PTPN6. Furthermore, mir-200c mediated the post-transcriptional repression of CDH17, impairing tumor migration. In vivo, LNP-enclosed mir-200c exhibited strong anti-tumor effects, further validating its therapeutic potential. Conclusions Mir-200c inhibits pancreatic cancer cell proliferation and migration through dual mechanisms: activation of PTPN6 transcription and repression of CDH17 expression. These findings suggest that mir-200c, particularly when delivered via LNP systems, may serve as a promising therapeutic strategy for pancreatic cancer.